Gauteng going dark: How nighttime light intensity changed during early stages of lockdown - Naidoo, Yashena; Maree, Gillian (Gauteng City-Region Obervatory, 2020)
The COVID-19 pandemic in South Africa has had far reaching impacts on society and the economy. A national disaster was declared on 15 March 2020 and by 26 March 2020 strong restrictive measures were put in place to manage the spread of the disease. The tightest restrictions were in place for lockdown level 5 which lasted from 26 March 2020 until the end of April 2020. During level 5 all movement was restricted and only essential workers were permitted to work. The country's borders were closed; interprovincial movement was banned; all gatherings except for small funerals were prohibited and schools, restaurants and non-essential businesses were closed. With movement restricted, activity was confined largely to domestic spaces. In the July 2020 Map of the month, we use nighttime satellite data to see whether night light intensity across the Gauteng City-Region reflects the impact of lockdown. We looked at how light intensity changed from before lockdown (March 2020) to lockdown level 5 (April 2020). In the full write up, we also show a second map of the difference between level 5 night light brightness (April 2020) and level 4 brightness (May 2020). The maps show a clear dimming of light intensity which resulted from reduced nighttime activity during the various lockdown levels. Roads were noticeably darker with far less vehicle traffic on main highways and many areas with usually vibrant activity at night were darker. As restrictions have eased, light intensity and nighttime activity have increased again across the GCR.
https://www.gcro.ac.za/outputs/map-of-the-month/detail/gauteng-going-dark/
Keywords: COVID-19; Night lights; Lockdown